Clinical and biochemical assessment of symptomatic and asymptomatic liver disease. (November 2019) - Collier, Jane
Abstract: Asymptomatic abnormal liver function tests (LFTs) are common, affecting 8% of the population. They are mainly caused by alcoholic liver disease and non-alcoholic fatty liver disease, whereas jaundice is most commonly caused by extrahepatic biliary obstruction, followed by alcoholic liver disease and acute liver injury from drugs or viruses. A careful history helps to exclude non-hepatic causes of abnormal LFTs, as well as indicating a potential hepatic cause. Cirrhosis can present with ascites or jaundice, the latter being common in alcoholic liver disease as a result of added injury from alcoholic hepatitis. Investigations in asymptomatic patients are intended to identify those with progressive liver disease, recognizing that cirrhosis can be clinically silent in the early stages. Concurrent clinical hepatomegaly, thrombocytopenia and splenomegaly warrant further investigation to exclude cirrhosis. An ultrasound scan and a serological chronic liver disease screen remain the standard investigations. Liver biopsy still has an important role to play in diagnosis, but other non-invasive markers of liver fibrosis can differentiate mild fibrosis from cirrhosis. Hepatitis E is becoming more common in the developed world as a cause of endemic acute hepatitis. Systemic immunoglobulin G4 disease/autoimmune pancreatitis should be considered in the differential diagnosis of cholestatic biochemistry.